Strength Improvement of Soft Clay Stabilised With Rice Husk Ash and RCC-15 Spent Catalyst Based on Unconfined Compressive Strength Performance (UCS) - Gaol, Esron Padiri Lumban; Syahril, Syahril; Akbardin, Juang (Journal of Green Science and Technology, 2026)
This study evaluates the effect of combining 12% rice husk ash (RHA) with varying percentages of RCC-15 spent catalyst (7%, 9%, 11%, and 13%) on the engineering properties of soft clay soil obtained from Cililin. Laboratory tests were conducted, including physical property characterization, compaction tests, and unconfined compressive strength (UCS) tests with curing periods of 0, 3, 7, and 14 days. The results show that the addition of RHA and RCC-15 improves soil compaction characteristics, indicated by an increase in maximum dry density and a reduction in optimum moisture content. Furthermore, the UCS values increased significantly with higher RCC-15 content and longer curing periods, reaching values between approximately 1.57 and 3.66 kg/cm² at 14 days. These improvements are attributed to mechanical densification and pozzolanic reactions between the stabilizing agents and soil minerals. This study emphasizes the synergistic application of agricultural and industrial waste materials for local soil stabilization, indicating that the combined use of rice husk ash and RCC-15 spent catalyst can enhance the engineering performance of soft clay while supporting sustainable and resource-efficient ground improvement practices.